Behavioral and pharmacological effects of phytochemicals in Cinnamomum verum bark extract for prevention of experimental murine coccidiosis - Murshed, Mutee; Alzaylaee, Hind; Ibrahim, Khalid Elfaki; Ammari, Aiman; Ahmed, Hani; Al-Quraishy, Saleh (Frontiers in Veterinary Science, 2025)
ObjectivesNatural products hold significant potential in combating parasitic infections. Parasites belonging to the genus Eimeria are responsible for coccidiosis, which affects a wide variety of livestock worldwide. The emergence of drug resistance to coccidia has prompted renewed efforts to discover novel chemicals for alternative therapeutic techniques. This research was conducted to evaluate the effectiveness of Cinnamomum verum bark extract (CVBE) on behavior and the treatment of eimeriosis in mice.MethodsThe study involved the examination of five groups of mice, with E. papillate sporulation oocysts (1 × 103) being utilized to infect three groups by experimental means. The first group was the control, the second group was administered at a dosage of 100 mg/kg of CVBE only to test toxicity, and the third was the infected positive control. The fourth group was treated daily with 100 mg/kg of CVBE, while the fifth group received 50 mg/kg of amprolium via gavage. All mice were sedated using CO₂ and subsequently dissected for sample taking. Results FT-IR analysis, conducted using a Thermo Scientific optical spectrometer, revealed that CVBE contains 18 different phytochemical components. The administration of CVBE led to a significant decrease in the number of oocysts produced in the feces. Additionally, the parasite stages exhibited morphometric changes, with decreases in the measures compared with those of the infected but not treated mice. This improvement was accompanied by large increases in the number of goblet cells, which provided additional support for the effectiveness of CVBE as anticoccidial agents.ConclusionThe findings indicate that Cinnamomum verum bark extract has effective effects in reducing the shedding of cysts, possesses anticoccidial, antioxidant, and anti-inflammatory activity against jejunum injury induced by the parasite Eimeria papillata.